2019
DOI: 10.5194/bg-16-4307-2019
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter contents and degradation in a highly trawled area during fresh particle inputs (Gulf of Castellammare, southwestern Mediterranean)

Abstract: Abstract. Bottom trawling in the deep sea is one of the main drivers of sediment resuspension, eroding the seafloor and altering the content and composition of sedimentary organic matter (OM). The physical and biogeochemical impacts of bottom trawling were studied on the continental slope of the Gulf of Castellammare, Sicily (southwestern Mediterranean), through the analysis of two triplicate sediment cores collected at trawled and untrawled sites (∼550 m water depth) during the summer of 2016. Geochemical and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 76 publications
0
23
1
Order By: Relevance
“…observed decreases in sedimentary chl a in the upper 1 cm immediately after trawling, of 41 and 83 % for pulse and tickler gears respectively. Also, OM depletion as a result of long term fishing has been reported, even at water depths beyond 500 m (Martín et al, 2014;Paradis et al, 2019), where comparisons between trawled and untrawled sites yielded a difference in OC between 20 and 60 % (Paradis et al, 2019). Our results contrast with studies that found enhanced OC concentrations in trawled areas (Palanques et al, 2014;Pusceddu et al, 2005;Sciberras et al, 2016), possibly due to differing hydrodynamic and morphological conditions of the North Sea compared to other areas.…”
Section: Organic Carbon Depletioncontrasting
confidence: 95%
See 2 more Smart Citations
“…observed decreases in sedimentary chl a in the upper 1 cm immediately after trawling, of 41 and 83 % for pulse and tickler gears respectively. Also, OM depletion as a result of long term fishing has been reported, even at water depths beyond 500 m (Martín et al, 2014;Paradis et al, 2019), where comparisons between trawled and untrawled sites yielded a difference in OC between 20 and 60 % (Paradis et al, 2019). Our results contrast with studies that found enhanced OC concentrations in trawled areas (Palanques et al, 2014;Pusceddu et al, 2005;Sciberras et al, 2016), possibly due to differing hydrodynamic and morphological conditions of the North Sea compared to other areas.…”
Section: Organic Carbon Depletioncontrasting
confidence: 95%
“…For this, the site-specific conditions such as rates of biogeochemical recovery and sedimentation rates would need to be investigated to fine-tune management (Paradis et al, 2019). Alternatively, areas with high denitrification rates, crucial for eutrophication mitigation can be closed to trawling completely, as done in other regions of the world (Ferguson et al, 2020).…”
Section: Reducing Gear Penetration Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…Impacts associated to bottom trawling include removal or damage to epibenthic fauna, reduction of habitat complexity and alteration of sedimentary and geochemical processes (e.g. De Leo et al, 2017;Hiddink et al, 2017;Paradis et al, 2019). With bottom trawling progressively expanding to deeper environments, VMEs associated to sedimentary bottoms have undergone a vast decimation (Sardà et al, 2004;Gerovasileiou et al, 2019;Pusceddu et al, 2014), restricting their distribution to isolated regions or areas inaccessible to trawlers, such J o u r n a l P r e -p r o o f as sub-vertical walls or regions surrounded by rocky outcrops (Bo et al, 2015;Pierdomenico et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show lower OC contents in surface sediments of trawled areas (Bhagirathan et al, 2010;Martín et al, 2014b;Paradis et al, 2019;Pusceddu et al, 2014), while others report higher OC contents, presumably due to fertilization brought about by resuspension or uplifting of OC from deeper layers caused by trawling (Palanques et al, 2014;Pusceddu et al, 2005). In the short term, demersal fishing-induced sediment disturbance stimulates OC mineralisation in cohesive sediments, likely due to the enhanced decomposition of previously buried refractory OC (van de Velde et al, 2018).…”
mentioning
confidence: 99%